Situation analysis of community pharmacy owners in Lebanon - Hallit S; Zeenny RM; Sili G; Salameh P. (Pharmacy Practice, 2017)
Objective: To evaluate the current community pharmacists’ interventions and job satisfaction, secondary to the alteration in the financial rewards. Methods: A cross-sectional study was carried out, using a proportionate random sample of Lebanese community pharmacy owners from all districts of Lebanon. Results: Out of 1618 distributed questionnaires, 1465 (90.5%) were collected back from pharmacy owners. Our study results showed that the monthly sales and profit decreased significantly in the last decade as well as the number of loyal customers (p<0.001 for all). The rent, the total assistant pharmacists’ and employees’ salaries, income taxes, municipality fees, the total bills (electricity, water, cleaning, security) and the disposal of expired products per year significantly increased during the last 10 years (p<0.001). 95% of the owners said they cannot afford to hire any more pharmacists while 45% said they cannot afford buying software for their pharmacies. Finally, 89% of these owners admitted that their situation was better 10 years ago compared to nowadays. Conclusion: Most Lebanese community pharmacists are not financially satisfied; their financial situation deteriorated in the last decade. The ministry of Health along with the Order of Pharmacists in Lebanon should cooperate together to resolve this problem since they are two entities responsible for the patient’s health.